(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Introduced in many universities quality management systems suggest the development of appropriate technologies for the assessment of learning results. Unfortunately, some of the real tasks remain outside the scope of the systems due to complexity, non-formalization, unawareness or lack of adequate mathematical models, software and more. Such is the task of attestation of the research and teaching staff, which is being periodically solved in universities. The work proposed model for the formalization of the problem of attestation of scientific and pedagogical staff, based on an adapted version of the one-parameter Rasch model for dichotomic data. The model allows software implementation and help to reduce the subjectivism in evaluating the performance of teachers in universities.